Regional aspects of small and medium entrepreneurship development - Minakov A. V. (Topical issues of law, economic and management, 2025)
In the context of geopolitical instability and economic turmoil, the study of regional development of small and medium-sized businesses is particularly relevant, since this sector plays a key role in innovation, job creation and economic growth. Business development in Russia varies significantly across regions due to many factors, including economic activity in the region, the level of infrastructure development, access to financing and support from the authorities. The purpose of the study is to study the regional aspects of small and medium-sized entrepreneurship development. The article uses such research methods as analysis of theoretical sources, study of statistical data, comparative analysis. The indicators characterizing the development of entrepreneurship, its financing and lending in the Republic of Tatarstan over several years were analyzed.
Keywords: малый бизнес; средний бизнес; малое предпринимательство; small and medium-sized businesses; поддержка МСП; региональная поддержка малого предпринимательства; развитие малого бизнеса; small entrepreneurship; support for SMEs; regional support for small entrepreneurship; small business development